Leadership : theory and practice - Northouse, Peter G. (Thousand Oaks : SAGE Publications, 2007)
DSU Title III 2007-2012.
Case 14.2 : How safe is safe? -- Case 14.3 : Reexamining a proposal -- Leadership instrument -- Perceived leader integrity scale (PLIS) -- Scoring -- Scoring interpretation -- Summary -- References -- Name index -- Subject index -- About the author -- About the contributors.
Includes bibliographical references and indexes.
Keywords: Leadership; Leadership -- Case studies; Leadership; Leadership -- Case studies